THE ORGANIZATION WORKS TO IMPROVE THE CLINICAL AND ECONOMIC OUTCOMES OF CARE FOR PROSTATE CANCER - O. I. Apolikhin; A. V. Sivkov; I. V. Chernishov; M. I. Katibov; O. V. Zolotukhin; I. A. Shaderkin; S. A. Leonov; D. A. Vojtko; M. Y. Prosyannikov (Исследования и практика в медицине)
Objective. Improving health outcomes in prostate cancer by developing optimal approaches to early detection, staging and treatment of disease. Materials and methods. Urologic care for patients with prostate cancer in the Voronezh region is divided according to the conception of the Program "Urology" into 4 of standardized, integrated stages. The first stage are primary care physicians. The purpose of this stage is a screening questionnaire for men of Voronezh region between the ages of 45 to 74 years using a modified international questionnaire lower urinary tract symptoms (IPSS) and nomograms individual risk of prostate cancer (SWOP №1).            In case of identification of risk groups for prostate cancer, patients were sent to the urologist at the place of residence, which is conducting special examinations (FRA, ultrasound of the kidneys, bladder, TRUS, UFW), forming a risk group for verification of diagnosis. Then the patient is directed to the second stage of inter-regional urology center (ITC), whose task in the diagnostic phase is to verify the diagnosis.    In case of confirmation of the diagnosis by an urologist of ITC there was created the interactive consultation on the basis of remote Advisory portal Nethealth.ru together with leading research Institute of urology and regional urology center they identified the clinical significance of the disease and subsequent treatment strategy. In case of the detection of clinically significant prostate cancer patient is sent to the third stage - Regional or an optional fourth stage (center providing PMF) - the Federal urology center, where he is treated with highly specialized medical care and conducted quality control.   In case of detection of clinically insignificant PC assistance was provided at the level of ITC (active surveillance, watchful waiting, hormone therapy on the recommendations of the oncourologist of regional urology center).Results. During the realisation of the Programme on the territory of theVoronezh region they deployed 7 Interdistrict (ITC) and 1 regional centre. The most difficult clinical cases were sent to the Federal urology center - research Institute of urology. They humiliated 140 experts from the region, with 80 of them they studied using remote sensing technology. For the realisation of the Program it was established an Advisory portal NetHealth.ru, which considered 498 clinical cases of prostate cancer, with 28 of specialists in various stages of the region took an active part in distance counseling.      From 2009 to 2013 an improvement of a number of indicators was marked: increase in the absolute number of patients with newly diagnosed prostate cancer from 451 to 603 cases, a localized increase in the share stages with 60.3% to 71.2 %, a decrease of deaths within one year from the date of diagnosis for prostate cancer from 14.6% to 6.5% and deaths among all registered patients with prostate cancer from 10.4% to 5.5%, reducing the proportion of clinically insignificant PCA from 36.4 to 14.1%.Conclusions. "PC module" of integrated phased standardized program "Urology" is a universal tool for solving the problems of improving the organization of medical care for prostate cancer, as well as the principles of operation can be used in other diseases of urology and other medical fields. Clinical and economic efficiency and the versatility of the basis for its recommendations as a priority in the organization of medical care at a cancer on the entire territory of the Russian Federation.